Household Words - Wexler, Peter (Meta, 1994)
Abstract A reading of Charles Dicken's weekly Household Words reveals at least 50 antedating of words for which the Oxford English Dictionary gives a 20th century dating. These words, from the early 1850's, are mostly of a technical nature. They are presented in context, together with their OED dating.